Coastal proximity and individual living standards: Econometric evidence from georeferenced household surveys in sub-Saharan Africa - Wild, Frederik; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2022)
We investigate georeferenced household-level dataconsisting of up to 128,609 individuals living in 11,261 localities across 17 coastal sub-Saharan African countries over 20 years. We analyze the relevance of coastalproximity, measured by the geographic distance toharbors, as a predictor of individual economic livingstandards. Our results highlight the role of human capital, urbanization, and infrastructural endowments in explaining within-country differences in individual economic welfare.
Keywords: Geography; Sub-Saharan Africa; Mediation (Statistics); Coastal Proximity; Mediation Analysis; Coastal Countries; Econometric Evidence; Household Survey